The Montreal Augmentation Mammaplasty Operation (MAMO) Simulator: An Alternative Method to Train and Assess Competence in Breast Augmentation Procedures. (3rd January 2018) - Kazan, Roy; Viezel-Mathieu, Alex; Cyr, Shantale; Hemmerling, Thomas M; Gilardino, Mirko S
Abstract: Background: Surgical residents' exposure to aesthetic procedures remains limited in residency training. The development of the Montreal augmentation mammaplasty operation (MAMO) simulator aims to provide an adjunctive training method and assessment tool to complement the evolving competency-based surgical curriculum. Objectives: To perform face, content, and construct validations of the MAMO simulator for subpectoral breast augmentation procedures and assess the reliability of the assessment scales used. Methods: Plastic surgery staff and residents were recruited to perform a subpectoral breast augmentation on the simulator. Video recordings of their performance were blindly evaluated using the objective structured assessment of technical skills (OSATS) system consisting of the global rating scale (GRS), mammaplasty objective assessment tool (MOAT), and a surgery-specific Checklist score. Results: Fourteen plastic surgery residents and seven expert plastic surgeons were enrolled. Experts' performance was significantly higher than residents' according to each of GRS, MOAT, and Checklist scores. Mean values of residents and experts were 23.4 (2.5) vs 36.9 (3.1) ( P < 0.0001) for GRS score, 30.4 (2.2) vs 40 (3.2) ( P < 0.0001) for MOAT scores, and 9.7 (1.5) vs 12 (1) ( P < 0.001) for Checklist scores, respectively. Face and content validations showed excellent results among parameters evaluated, with an overall mean score of 4.8 (0.3) on 5. Cronbach's alpha was 0.96 and 0.83 for GRS and MOAT scores, respectively. Intraclass correlation coefficients for interrater reliability were excellent at 0.93, 0.92, and 0.89 for the GRS, MOAT, and Checklist scores, respectively. Conclusions: This study proves the construct simulator to be valid and the assessment scales to be reliable.